No country for native crayfish: importance of crustaceans in the diet of native and alien Northern raccoons. Issue 6 (2nd November 2021) - Boncompagni, Luca; Molfini, Marco; Ciampelli, Paola; Fazzi, Paola; Lucchesi, Marco; Mori, Emiliano; Petralia, Lorenzo; Mazza, Giuseppe
Abstract : The Northern raccoon Procyon lotor is a native mesocarnivore of North America which has been introduced to many Eurasian countries, where invasive populations currently occur. Regarding Italy, the species is present in Lombardy and in the Foreste Casentinesi National Park (Tuscany and Emilia-Romagna). In this work, we conducted a review on food habits of the Northern raccoon both in the native and in the introduced ranges, and we firstly reported the evidence on the impact of this species on native crayfish in Central Italy. We retrieved 18 papers published between 1932 and 2020, 14 from the native range and four from the invasive range. We analysed the frequency of occurrence of nine food categories (mammals, birds, reptiles, amphibians, fish, insects, crustaceans, fruits, and others). After fruits, crustaceans (where available) were the main food items detected in raccoon scats (up to 60% of the total diet, in the frequency of occurrence). In September 2019, we detected a total of 37 dead adult freshwater white-clawed crayfish Austropotamobius pallipes complex in Central Italy, with evident signs of predation by the Northern raccoon. The local population of Northern raccoon is fast expanding its range, whereas the local population of A. pallipes complex is declining. This crayfish species is protected by national and international laws. Thus, a monitoring program involving all stakeholders and institutions dealing with in environmental management, aiming at removing all raccoons currently present in this area of Central Italy, should be carried out in the short term to limit the potential impacts exerted by the fast-spreading of this invasive mammal.